Analisis Pengaruh Variabel Makroekonomi Terhadap Cadangan Devisa Negara Indonesia Menurut Perspektif Ekonomi Islam Periode Triwulan I-III 2023 - Petty Christin Mahgaraini; Nurul Cahya Arsita (Pusat Riset dan Inovasi Nasional, 2024)
This study provides an explanation of the macroeconomic variables of export variables, the rupiah exchange rate against the US dollar, and foreign debt to Indonesia's foreign exchange reserves during 2023 which began in January and ended in September in accordance with the Islamic economic perspective. This study uses time series data published by the Central Bureau of Statistics and Bank Indonesia as the author's data source. The data Analysis tool using software Eviews 12 with classical assumptions and statistical tests. The results showed that exports, the rupiah exchange rate against the US dollar and foreign debt had no significant effect on the country's foreign exchange reserves in 2023 due to fluctuations .